Moving to lower-poverty neighborhoods offers broad benefits for children with asthma, regardless of sex or other baseline characteristics - Torie L. Grant, MD, MHS; Laken C. Roberts Lavigne, PhD, MPH; Craig Evan Pollack, MD, MHS; Pete Cimbolic, BA; Susan Balcer-Whaley, MPH; Roger D. Peng, PhD; Elizabeth C. Matsui, MD, MHS; Corinne A. Keet, MD, PhD (Journal of Allergy and Clinical Immunology: Global)
Background: It was previously found that moving to lower-poverty/higher-opportunity neighborhoods as part of a housing mobility program was associated with improvements in asthma exacerbations and symptoms among children with asthma. Whether some subsets of children with asthma experience a greater improvement in asthma morbidity after moving is unknown. Objective: Our aim was to determine whether the benefits of moving to lower-poverty/higher-opportunity neighborhoods were concentrated in subsets of participants with asthma. Methods: We conducted a secondary analysis of the participants in the Mobility Asthma Project. Generalized estimating equations were used to assess the association between moving and asthma exacerbations and maximum symptom days. Separately, these models were then stratified by sex, age, body mass index, allergic sensitization, asthma severity, and stress before the move to estimate stratum-specific odds ratios for moving. Results: Participants broadly experienced a postmove reduction in odds of an exacerbation and maximum symptom days. Male children and children at a higher asthma controller medication treatment step experienced a greater reduction in maximum symptom days with moving. Conclusion: Children with asthma experience a reduction in odds of an exacerbation and symptoms after moving to lower-poverty/higher-opportunity neighborhoods. These improvements in asthma outcomes are seen regardless of baseline sex, age, body mass index, allergic sensitization, asthma severity, and premove stress.